Validation of a Kannada version of the Impact of Events Scale (IES) - Tavane, Prashanth N (International Society of Preventive and Community Dentistry, 2013)
Background: This study presents a Kannada translation and validation of the Impact of Event Scale in a population of men and women exposed to maxillofacial trauma and orthopedic/ general trauma. Materials & Methods: A total of 96 study subjects from multi modal trauma centers in Bangalore city completed the Kannada translated questionnaire at the time of discharge, the first post- operative month and the sixth month of follow up. Results: The Kannada IES is reliable when analyzed with the students T-test, it has good internal consistency with Cronbach's α-coefficients ranging from .970 to .974, the test-retest reliability with Karl Pearson's correlation of the scale at all three time intervals showed significant correlation. A principal component analysis was conducted to ascertain the validity and two components were derived from the 15 questions which were able to explain 88% of the variation and the two were retained (intrusion and avoidance). Conclusion: The Kannada version of the IES has satisfactory reliability, internal validity, test-retest reliability and the factor structure was similar to the proposed theoretical structure of the IES. How to cite this article: Tavane PN, Raghuveer HP, Kumar RD, Shobha ES, Rangan V, Dutt CS. Validation of a Kannada version of the Impact of Events Scale (IES). J Int Oral Health 2013; 5(5):38-47.